Synovial sarcoma: A radiologic case report - Neenu Kuruvilla, MD; Brandon Thinh Duc Dang, MD; Joseph Dobtsis, MD (Radiology Case Reports)
Synovial sarcoma is a common but aggressive subset of sarcomatous tumors that often arises adjacent to the large joints of extremities. We present a case of a 33-year-old male with no medical history and an initial complaint of right leg pain. On further radiological and pathological investigation, he was diagnosed with synovial sarcoma in the medial soft tissues of his thigh. This article aims to provide a comprehensive overview of synovial sarcoma's radiological and histologic characteristics.